2015
DOI: 10.1111/jnc.13262
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted microvascular endothelial cells promote oligodendrocyte precursor cell survival in ischemic demyelinating lesions

Abstract: We previously showed that transplantation of brain microvascular endothelial cells (MVECs) greatly stimulated remyelination in the white matter infarct of the internal capsule (IC) induced by endothelin-1 injection and improved the behavioral outcome. In the present study, we examined the effect of MVEC transplantation on the infarct volume using intermittent magnetic resonance image and on the behavior of oligodendrocyte lineage cells histochemically. Our results in vivo show that MVEC transplantation reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…We confirmed our previous study reporting that MVEC-CM reduced apoptotic cell death of OPCs [ 4 ], and found that MVEC-CM promoted their motility ( Fig 1 ). ECs are active and dynamic cells producing various biologically active molecules in response to various stimuli.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We confirmed our previous study reporting that MVEC-CM reduced apoptotic cell death of OPCs [ 4 ], and found that MVEC-CM promoted their motility ( Fig 1 ). ECs are active and dynamic cells producing various biologically active molecules in response to various stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, in serum-free medium (control) and EV-dep-MVEC-CM, many OPCs died with the typical morphological features of apoptosis including pyknotic nuclei. As we reported previously, MVEC-CM had no apparent effect on OPC differentiation [ 4 ].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…We previously reported that MVEC transplantation increased the number of OPCs by inhibiting apoptotic death in the rat model of white matter infarct (Iijima et al, ). We also reported that EVs secreted from endothelial cells promoted survival, proliferation and motility of cultured OPCs (Kurachi et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Guo et al [ 54 ] demonstrated that secretion of brain-derived neurotrophic factor (BDNF) by CECs was vital for neuroprotection. In addition, soluble factors secreted by CECs were found to enhance the proliferation of oligodendrocyte progenitor cells (OPC); which are precursors of oligodendrocytes as well decrease apoptotic OPC death in vitro [ 55 , 56 ]. Furthermore, extracellular vesicles derived from rat brain CECs were shown to have a role in promoting OPC survival, proliferation and motility in a dose-dependent manner [ 57 ].…”
Section: Background: the Blood–brain Barrier As Part Of The Neurovascmentioning
confidence: 99%